(untitled) (Global Journal of Human-Social Science, 2012)
Population increase coupled with the rise in demand for construction materials like granite and gravel have necessitated the continued growth of quarry activities in and around the Abeokuta Metropolis, southwestern, Nigeria. The results of the questionnaire survey carried out on the quarry workers in three selected quarry sites (abandoned colonial, AGI and Oba) revealed that over 70% of the entire working force were mainly women who work as casual labourers crushing or sorting stones in the quarries. The ages of the female quarry workers ranges between 10-60 years, with majority of them having little or no formal education. Many have spent between 10-20 years of their life in the quarries using primitive tools and being paid pittance, which is not comparable with the work done. They often work for about 12 hours daily crushing and average of 10 headpan of stone per day, which attracts about N10 per headpan. Majority of the women are from polygamous family which further push them into poverty as the wages received from the quarry work is not enough to take care of their needs. Polygamy exacerbates the impoverishment of women by limiting their access to financial resources. These women are at the risk of health problems such as severe chest and joint pains, headache, fever, catarrh and rheumatism which affect their productivity. There is a need for the empowerment of these women through education as a means of challenging patriarchal ideology of male domination especially in employment and wages.